In search of the autonomous and critical individual: a philosophical and pedagogical analysis of the physical education curriculum of São Paulo (Brazil) - Betti, Mauro [UNESP]; Knijnik, Jorge; Venancio, Luciana [UNESP]; Neto, Luiz Sanches [UNESP] (Routledge Journals, Taylor &francis Ltd, 2015)
Background: Academics, teachers and policy-makers across the world have discussed how to develop a relevant physical education (PE) curriculum that addresses the 'body education'needs and interests of twenty-first-century students. In Brazil, after the launch of the national curricular parameters (PCNs) in the late 1990s, many new PE curricula have emerged, some, such as the curriculum of the state of Sao Paulo (SP), claiming to be truly innovative in the promotion of the autonomous and critical individual. In 2006, SP, as the richest and most populous Brazilian State, convened several groups of specialists to design new curricula in all school areas, including PE. Curricula proposals always have a set of underpinning values and philosophies and the PE curriculum in SP seems to have enhanced its school function to beyond the sports restricted interests.Purpose: This article aims to examine the philosophical and pedagogical directions that support the new PE curriculum in SP. It asks on what concepts of culture, body and movement the Sao Paulo physical education (SP/PE) curriculum is based; how the education of the autonomous individual is conceptualised and how the curriculum enhances the teaching of students'body practices. It also considers the ways in which autonomy is lived in an environment historically marked by social inequality.Research design: In reflecting on these questions this paper adopts the notion of one's own body as a 'unit of meaning'). It also draws on concept of education as the development of a critique of reality as the basis for transforming it. It discusses movement culture (MC), a central idea in the SP/PE curriculum derived from these practices of critique and transformation, as well as the concept of Sich-Bewegen, which emphasises movement as a proper expression of the individual.Conclusions: The traditional notion of being 'physically educated'as proposed by Corbin has been superseded in the new curriculum. It appears that the SP/PE curriculum is challenging educators to address new key issues in their educational practices: to foster critical thinking about both the content and themes addressed by the PE curriculum; to consider cultural diversity whilst teaching; to move away from standardised proposals; and to enhance, in students, critical views of the MC content presented in the media, and thereby to encourage students to take into account the media thematic axis as a starting and an ending point for their educational practices.
Keywords: Phenomenology; Emancipatory pedagogy; Physical education curriculum; Brazilian physical education; Dialogic pedagogy